Efektivitas media pembelajaran video tutorial terhadap hasil belajar mahasiswa pada Matakuliah IPA Sekolah - Ratnawaty Mamin; Rifda Nur Hikmahwati Arif (Seminar Nasional LP2M UNM, 2019)
This study aimed to describe; (1) The learning outcomes of science department students of Makassar State University on school science courses using video tutorial based learning media; (2) The effectiveness of using tutorial video-based learning media on learning school science courses. This research is a one-shot case study experimental study. The instruments used in the study were observation sheets, questionnaires, and test results. Data analysis techniques were carried out by descriptive statistics and inferential statistical analysis. The results of the study concluded that; (1) The learning outcomes of science department students of Makassar State University towards school science courses after using a practical video tutorial based learning media are also said to be quite good, this is evidenced by the average students values of 75.4; (2) The use of tutorial video-based learning media on School Science course learning will be effective if it is applied in the school's science class. This is evidenced by the H0 value which stated that the highest learning outcomes is 70% rejected, because the student learning outcomes exceed 70% which is 76.95%.